A Tale of Two Programs for Parents of Young Children: Independently-Conducted Case Studies of Workforce Contributions to Scale in Bhutan and Rwanda - Frances Aboud; Karma Choden; Michael Tusiimi; Rafael Contreras Gomez; Rachel Hatch; Sara Dang; Theresa Betancourt; Karma Dyenka; Grace Umulisa; Carina Omoeva (MDPI AG, 2023)
Two case studies of parenting programs, aiming to improve parenting practices and child development outcomes, and implemented by Save the Children/Ministry of Health/Khesar Gyalpo University in Bhutan and Boston College/University of Rwanda/FXB in Rwanda, respectively called Prescription to Play and Sugira Muryango, were conducted by an independent research and learning group. Implementation research focused on the workforce, a crucial but little-studied element determining the success of programs going to scale. Mixed methods were used to examine their training, workload, challenges, and quality of delivery. Health assistants in Bhutan and volunteers in Rwanda were trained for 10-11 days using demonstrations, role plays, and manuals outlining activities to deliver to groups of parents (Bhutan) or during home visits (Rwanda). Workers' own assessments of their delivery quality, their confidence, and their motivations revealed that duty, confidence, and community respect were strong motivators. According to independent observations, the quality of their delivery was generally good, with an overall mean rating on 10 items of 2.36 (Bhutan) and 2.44 (Rwanda) out of 3. The facilitators of scaling for Bhutan included institutionalizing training and a knowledgeable workforce; the barrier was an overworked workforce. The facilitators of scaling for Rwanda included strong follow-up supervision; the barriers included high attrition among a volunteer workforce.